2021
DOI: 10.1155/2021/8879227
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Dietary Omega-3 Polyunsaturated Fatty Acids, the Gut Microbiota, and Intestinal Immunity

Abstract: Omega-3 polyunsaturated fatty acids (omega-3 PUFAs), which are essential fatty acids that humans should obtain from diet, have potential benefits for human health. In addition to altering the structure and function of cell membranes, omega-3 PUFAs (docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), alpha-linolenic acid (ALA), and docosapentaenoic acid (DPA)) exert different effects on intestinal immune tolerance and gut microbiota maintenance. Firstly, we review the effect of omega-3 PUFAs on gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 104 publications
6
143
0
2
Order By: Relevance
“…The n-3PUFA are thought to affect the gut microbiota mainly through regulation of the type and amount of bacteria in the gut, changes in the levels of inflammatory mediators such as endotoxin and interleukin, and regulation of SCFA concentrations 33 . In this study, compared with the SOY group, the EPA and DHA groups had significantly lower the Chao-1 and Observed_species indices, which are used to estimate species richness abundance-based estimator of species richness at the genus level Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The n-3PUFA are thought to affect the gut microbiota mainly through regulation of the type and amount of bacteria in the gut, changes in the levels of inflammatory mediators such as endotoxin and interleukin, and regulation of SCFA concentrations 33 . In this study, compared with the SOY group, the EPA and DHA groups had significantly lower the Chao-1 and Observed_species indices, which are used to estimate species richness abundance-based estimator of species richness at the genus level Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As these two biosynthetic pathways share enzymes for their respective dehydration and elongation steps, they are antagonistic to each other. In general, a high 18:3n3 (n-3 fatty acid) diet is correlated with positive physiological effects whereas a high 18:2n6 (n-6 fatty acid) diet is correlated with metabolic dysbiosis and negative physiological effects [74, 75] . Accordingly a balanced dietary intake of n-6/n-3 fatty acids is recommended to be 1:1-2:1, although the average ratio in a typical Western diet has been reported to be >15:1 [76] .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, open-label, cross-over trial providing 4 g/day of the combination of DHA and EPA (or 2 g DHA) in TG or EE form to healthy volunteers for 8 weeks reported that both DHA forms significantly increased the abundance of several beneficial genera (Watson et al, 2018), such as Bifidobacterium, Roseburia, and Lactobacillus, which are the main producers of butyrate in the gut. Butyrate is regarded as an important nutrient for the colonic mucosa, which in turn modulates gene expression, inflammation, differentiation, and apoptosis in host cells (Fu et al, 2021). Younge et al (2017) observed that there were an increase in bacterial diversity and a decrease in the abundance of Streptococcus, Clostridium, and many pathogenic genera within Unless it is specified, the recommendation is for DHA alone.…”
Section: Prebioticsmentioning
confidence: 99%